2009
DOI: 10.1021/ma900270u
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Micellar Solutions of Polystyrene-block-polybutadiene and Polystyrene-block-polyisoprene in Propane Exhibit Cloud-Pressure Reduction and Distinct Micellization End Points

Abstract: Micellar solutions of polystyrene-block-polybutadiene and polystyrene-block-polyisoprene in propane are found to exhibit significantly lower cloud pressures than the corresponding hypothetical nonmicellar solutions. Such a cloud-pressure reduction indicates the extent to which micelle formation enhances the apparent diblock solubility in near-critical and hence compressible propane. Concentration-dependent pressure-temperature points beyond which no micelles can be formed, referred to as the micellization end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The micellization in propylene is at least 300 bar lower than that in propane. More subtle cloud-point and micellization phenomena for this S-B copolymer observed at higher temperatures, above 170°C in propane and above 140°C in propylene, as these systems approach a critical micellization temperature, are being documented in a separate project [22].…”
Section: Micellization and Cloud Point Of S-b Diblock Copolymer Stronmentioning
confidence: 86%
See 1 more Smart Citation
“…The micellization in propylene is at least 300 bar lower than that in propane. More subtle cloud-point and micellization phenomena for this S-B copolymer observed at higher temperatures, above 170°C in propane and above 140°C in propylene, as these systems approach a critical micellization temperature, are being documented in a separate project [22].…”
Section: Micellization and Cloud Point Of S-b Diblock Copolymer Stronmentioning
confidence: 86%
“…This is because the polybutadiene block in S-B may thermally decompose at higher temperatures, as explained in Ref. [22].…”
Section: Copolymer Hydrogenation Effect On Propylene Solutionmentioning
confidence: 92%
“…The copolymer cloud-pressure curve consists of two distinct branches, a conventional cloud-pressure (CP) branch above the micellar end point (MEP, a pressure-generalized critical micelle temperature) and a micellar cloud-pressure (MCP) branch below MEP. 2 At CP, we observe the onset of copolymer precipitation upon decompression of a random nonmicellar solution. At MCP, we observe the onset of copolymer precipitation upon decompression of a micellar solution.…”
Section: Introductionmentioning
confidence: 89%
“…At MCP, we observe the onset of copolymer precipitation upon decompression of a micellar solution. The previous work demonstrated that MCP is consistently lower than CP estimated for a hypothetical random solution 2,3 and that it is not very sensitive to the diblock molecular weight, composition (block ratio), or concentration. This is in contrast to the micellization pressure (MP), which depends on the diblock molecular weight, composition (block ratio), and concentration.…”
Section: Introductionmentioning
confidence: 93%
“…In comparison with the impact of temperature, the effects of pressure on micellization of block copolymers have been less explored, in part due to difficulties in sample environments . Previous studies utilize supercritical CO 2 (scCO 2 ), near‐critical propane, near‐critical trifluoromethane, and dimethyl ether, and so on to manipulate micellization of block copolymers. The solvent quality in these studies varies largely with pressure since they are highly compressible within the accessible experimental window.…”
Section: Introductionmentioning
confidence: 99%